Design and Implementation of ERP System Based on SSM Framework - Zhang, Lina; Wang, Changchun; Cao, Jixiang (IOP conference series. Earth and environmental science, 2020)
With the continuous development of enterprise information technology, information resource sharing has become a major subject of scientific research projects. Traditional enterprises have complex business processes, low management efficiency and high operation cost, which leads to enterprises of low competitiveness. Therefore, it is the best choice for enterprises to regain their core competitiveness to use ERP management system to improve their operation process, simplify their operation and make their operation methods transparent. This paper designs an ERP system based on SSM framework. This paper introduces the basic principles of SSM framework, respectively realizes the business functions of Controller layer, Service layer and DAO layer in the framework, and designs Web pages for data collection and display. The main components of the system consist of six modules: purchase plan, purchase order, purchase contract, purchase document inquiry, purchase to order and purchase return, which can well realize the actual requirements of enterprises.